Hubungan Wilayah Tempat Tinggal dengan Pengetahuan Anemia pada Remaja Putri di Indonesia - Winny Kirana Hasanah (Universitas Malahayati, 2023)
ABSTRACT In Indonesia, the incidence of Anaemia in 2018 was higher among women than men. Based on age group, adolescence ranked third highest in Anaemia with a prevalence of 32 percent. Anaemia is more prone to occur in adolescent girls compared to adolescent boys. The purpose of this study was to analyze the relationship between type of residence and knowledge of Anaemia among Indonesian adolescent girls. This study used a cross-sectional design using secondary data from IDHS Adolescent Reproductive Health in 2017. The sample size was 10,649 female adolescent respondents who were taken using the total sampling technique. Data analysis used Multiple Logistic Regression statistical test. The study showed that 74.7% of adolescent girls living in rural areas and 62.1% of adolescent girls in urban areas had insufficient knowledge related to Anaemia. The results of multivariate analysis stated that there was a significant relationship between region of residence and knowledge about Anaemia among adolescent girls in Indonesia (p=0.0001; OR=1.8; CI: 1.7-2.0). Adolescent girls living in urban areas were 1.8 times more likely to have good Anaemia knowledge than those in rural areas.Keywords : adolescent girls, Anaemia knowledge, rural, urban ABSTRAK Angka kejadian Anemia di Indonesia tahun 2018 pada wanita lebih tinggi daripada laki-laki. Berdasarkan kelompok umur, usia remaja menduduki peringkat ketiga Anemia tertinggi dengan prevalensi 32 persen. Anemia lebih rentan terjadi pada remaja putri dibandingkan dengan remaja laki-laki. Tujuan dari penelitian ini untuk menganalisis hubungan wilayah tempat tinggal dengan pengetahuan Anemia pada remaja putri Indonesia. Studi ini menggunakan desain cross-sectional menggunakan data sekunder SDKI Kesehatan Reproduksi Remaja 2017. Besar sampel sebanyak 10.649 responden remaja putri yang diambil menggunakan teknik total sampling. Analisis data menggunakan uji statistik Regresi Logistik Ganda. Penelitian menunjukkan sebesar 74,7% remaja putri yang tinggal di perdesaan dan 62,1% remaja putri di daerah perkotaan memiliki pengetahuan yang kurang terkait Anemia. Hasil analisis multivariat menyatakan terdapat hubungan yang signifikan antara wilayah tempat tinggal dengan pengetahuan tentang Anemia pada remaja putri di Indonesia (p=0,0001; OR=1,8; CI: 1,7-2,0). Remaja putri yang tinggal di daerah perkotaan 1,8 kali lebih mungkin memiliki pengetahuan tentang Anemia yang baik daripada remaja di daerah perdesaan.Kata kunci: remaja putri, pengetahuan Anemia, perdesaan, perkotaan